2016
DOI: 10.1093/humrep/dew282
|View full text |Cite
|
Sign up to set email alerts
|

A mild ovarian stimulation strategy in women with poor ovarian reserve undergoing IVF: a multicenter randomized non-inferiority trial

Abstract: May 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 30 publications
6
54
1
1
Order By: Relevance
“…None of our cases that developed OHSS had a GnRHa-trigger, consistent with the studies by Decleer et al 20 and Humaidan et al 21 and Kol et al 22 . Griesinger et al 23 obtained a reduced incidence of mild and moderate OHSS using a GnRHa-trigger, and only one cases out of 1924 women had an OHSS event.…”
Section: Discussionsupporting
confidence: 92%
“…None of our cases that developed OHSS had a GnRHa-trigger, consistent with the studies by Decleer et al 20 and Humaidan et al 21 and Kol et al 22 . Griesinger et al 23 obtained a reduced incidence of mild and moderate OHSS using a GnRHa-trigger, and only one cases out of 1924 women had an OHSS event.…”
Section: Discussionsupporting
confidence: 92%
“…So far, several papers attempting mild ovarian stimulation protocols in women with low ovarian reserve have been published from some clinical facilities . Taking these currently widely practiced methods into consideration, we basically left the choice of an ovarian stimulation protocol to the request of the patients after fully explaining the pros and cons of each protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Progressive improvements in embryology now allow for good pregnancy outcomes after using milder stimulation regimes with deliberately lower oocyte yields. Three randomised controlled trials in women considered to be poor responders to ovarian stimulation have shown similar pregnancy rates with mild ovarian stimulation versus the standard high-dose stimulation regimens, [27][28][29] contradicting the concept that high FSH doses might improve the outcome for such patients. Similarly, a recent randomised controlled trial assessing women with predicted hyper-response undergoing IVF/ICSI with a reduced FSH dose (100 IU/ day) compared with standard dose (150 IU/day), resulted in similar cumulative live birth rates and, importantly, lower rates of OHSS, although not of severe OHSS.…”
Section: Mild Stimulation Regimesmentioning
confidence: 99%